Caracterização da gordura da amêndoa da gordura de cupuaçu (Theobroma grandiflorum S.) obtida por extração aquosa enzimática - SILVA, Danylla Cássia Sousa (Universidade Federal do Pará, 2024)
Aqueous enzymatic extraction is considered an emerging green technique that is being extensively investigated. In this work, cellulase, pectinase and protease enzymes are used in the aqueous extraction process of cupuassu fat, aiming to obtain a higher extraction yield. Different incubation systems were tested, at a temperature of 60 °C and following extraction kinetics (2 to 8 hours). The samples that obtained the highest fat extraction efficiencies were analyzed: aqueous phase, in terms of phenolic compounds and antioxidant activity, and oily phase (fats) characterized in terms of physicochemical properties, fatty acid profile, oxidative stability, thermal and bioactive compounds. The aqueous phase showed higher concentrations of phenolic compounds and antioxidant activity when compared to the oil phase. The fat samples showed approximate contents of monounsaturated and saturated fatty acids with higher concentrations of oleic and stearic, showed good oxidative stability (about 14 h) and thermal stability (close to 406 oC) and the best yield result (80.86 %) was achieved with the protease enzyme within 6 hours of incubation. The results indicated that cupuassu fats obtained by enzymatic aqueous extraction have potential for use in the food, pharmaceutical and cosmetics sectors.